To solve the first equation -5 + 2x = 1, we need to isolate the variable x by performing the following steps:
1. Add 5 to both sides of the equation:
-5 + 5 + 2x = 1 + 5
2x = 6
2. Divide by 2 on both sides to solve for x:
2x / 2 = 6 / 2
x = 3
Therefore, the solution to the first equation is x = 3.
To solve the second equation 3 - 5x = 7, we need to isolate the variable x by performing the following steps:
1. Subtract 3 from both sides of the equation:
3 - 3 - 5x = 7 - 3
-5x = 4
2. Divide by -5 on both sides to solve for x:
(-5x) / -5 = 4 / -5
x = -4/5
Therefore, the solution to the second equation is x = -4/5.
-5+2x=1
3-5x=7
1 answer